Who Moderates? A Polycentric Framework for Allocating Regulatory Responsibility in Online Content Moderation - El Wishi, Farh A. (AUC Knowledge Fountain, 2026)
The question of who is responsible for content moderation on the internet remains one of the key topics relating to internet governance. Legislation has been adopted, platforms have utilized self-regulation methods, and users have flagged and reported content, all often happening simultaneously, yet rarely according to any coherent principle for deciding which actor should bear primary responsibility for which aspect of the problem. This research argues that the absence of a principled allocative framework is the central governance failure of the internet's regulatory history, and that addressing it requires a structured distribution of regulatory responsibility across the three actors who actually govern content moderation. Drawing on Keller's three theoretical debates on internet regulation, Medzini's polycentric governance model, and the emerging judicial recognition in KGM v. Meta Platforms, Inc. (2026), this research proposes a three-tier polycentric framework grounded in a reserved exceptionalist theoretical position. Tier 1, governments, set the mandatory legal floor, including platform design obligations that fall outside Section 230's protection. Tier 2, platforms, govern the grey zone of potentially harmful but lawful content within procedural accountability requirements, with the Digital Services Act identified as the current best practice model. Tier 3, users, provide ground-level norm enforcement and participatory accountability, constituting an operative rather than merely advisory governance layer.